Enhancing methane recovery by intermittent substrate feeding and microbial community response in anaerobic digestion of glycerol. (March 2023) - Vikromvarasiri, Nunthaphan; Koyama, Mitsuhiko; Kurniawan, Winarto; Pisutpaisal, Nipon; Nakasaki, Kiyohiko
Abstract: Accumulation of intermediate volatile fatty acids, especially propionic acid, is a limiting factor in anaerobic digestion of glycerol. To mitigate this problem, intermittent substrate feeding was investigated and evaluated. The results showed that intermittent substrate feeding could decrease the effects of high concentrations of propionic acid and improve the performance of CH4 production at high substrate loading rates. CH4 production rate with intermittent substrate feeding (1.60 NL/L/day) was higher than single substrate feeding (1.47 NL/L/day) at 5.0 g COD/L/day of glycerol loading rate. NGS and PICRUSt were applied to monitor the changes in the microbial community. The proportion of dominant bacteria changed with alterations in glycerol loading rate and substrate feeding technique. NGS results elucidated three main bacterial groups that degraded and competed for glycerol, namely: Delftia, Trichococcus, and Desulfuromonas . Trichococcus and Desulfuromonas tended to withstand a higher rate of glycerol loading than Delftia . PICRUSt results demonstrated that Trichococcus is paramount in the glycerol degradation. Delftia and Desulfuromonas might compete with methanogens by utilizing acetate and/or H2 . This study suggested the role of microbial communities in CH4 production from glycerol. The intermittent feeding, which balanced organic acid production and its consumption, was clarified to improve methane production from glycerol.